Studies on the Physiology of Digestion in the last Instar Larva of the Rice Moth (Corcyra cephalonica Stainton). II. Digestive enzymes and effect of starvation on their secretion (Lepidoptera: Galleriidae). - Srivastava, P. N. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Out of the entire alimentary canal the mid-gut epithelium is the only part which secretes digestive enzymes amylase, invertase, maltase, lipase and trypsin, in the larva of Corcyra cephalonica Stainton. Enzymes are regurgitated even during starvation, though the secretion of some of these enzymes is stopped in the larvae starved for 5 days. Stimulus of feeding is required for the secretion of maltase, lipase and trypsin, where as amylase and invertase do not need the stimulus of feeding for their secretion.